P113 Indeterminate IGRA results prior to anti-tnf therapy: stable state testing may be important for immune-mediated inflammatory disorders. (15th November 2016) - Ibrahim, W; Abunga, Y; Mamo, J; Beck, S; Brij, SO
Abstract : Introduction: Screening for active tuberculosis (TB) and latent TB infection (LTBI) is mandatory prior to the initiation of anti-TNF therapy in patients with immune-mediated inflammatory diseases (IMID). In 2010, our local guideline included QuantiFERON®-TB Gold (QFT) as well as clinical risk stratification. However, indeterminate QFT results were increasingly identified in this population, higher than that observed in other published series. Aims: To identify patient and IMID characteristics that may be contributing to inderterminate QFT results and LTBI diagnostic uncertainty. Methods: We conducted a retrospective study of all patients that had received at least one dose of anti-TNF since 2010. Data obtained included patient demographics, TB risk stratification and QFT results. Results: 181 patients (M:F 87:94; age range 11–83; average age 44.8 years) had received at least one dose anti-TNF and were included in this study (see Table). The majority of patients had colitis (n = 143; 79%). 52 patients (28.7%) did not have a documented QFT or IGRA (interferon gamma release assay) result. LTBI was diagnosed in 8 (6.2%) with reactive QFT of whom 7 completed chemoprophylaxis and 1 was referred for further investigation and treatment elsewhere. 95 (73.6%) were QFT non-reactive. 26 (20.2%) were QFT indeterminate, all of whom had a diagnosis of colitis. Colitis patients were more likely to be QFT indeterminate if they were tested at the time of rescue anti-TNF with or without surgery (RR 5.71; 95% CI: 2.49–13.09; p < 0.0001). 2 patients who received rescue anti-TNF and were subsequently found to be QFT reactive, successfully completed LTBI chemoprophylaxis. Conclusion: The rate of indeterminate QFT results is higher than expected in our cohort of patients with colitis who require rescue anti-TNF therapy and is likely to be related to the timing of testing. If QFT testing is undertaken, this should be performed when patients are at stable state and not at the time of inflammatory crisis.